Using Data Assimilation to Reconstruct High‐Latitude Polar Cap Patches. Issue 6 (4th June 2020) - Negale, Michael; Holmes, Jeffrey; Parris, Richard; Ober, Daniel; Dao, Eugene; Kelly, Ralph; Eccles, J. Vincent; Hines, Jack; Pedersen, Todd
Abstract: Discrete high‐density plasma structures in the Earth's ionosphere that convect across the polar cap from the dayside to nightside are known as polar cap patches. This high‐latitude phenomenon can interfere and disrupt satellite and high‐frequency (HF) communications when the associated sharp electron density gradients are encountered, and therefore, accurate modeling and forecasting of such events would be greatly beneficial. In this study, we have utilized the assimilative Global Positioning System Ionospheric Inversion (GPSII) method to reconstruct the high‐latitude ionosphere utilizing data from Global Navigation Satellite System (GNSS) receivers, vertical ionosondes, the Resolute Bay Incoherent Scatter Radar (RISR‐N), in situ satellite data, and Super Dual Auroral Radar Network (SuperDARN) radars. The novel method of assimilating RISR‐N and SuperDARN ground scatter measurements helps to increase the limited number of observations at high latitudes. The reconstructed polar cap patches are shown to correspond with ground‐ and spaced‐based observations, illustrating the ability of utilizing GPSII to study the complex high‐latitude region. Key Points: Using the Global Positioning System Ionospheric Inversion (GPSII) method, we reconstructed the high‐latitude ionosphere on 22 January 2012 Polar cap patches were observed in the ionospheric reconstructions The reconstructed patches corresponded well to ground‐based and space‐based ionospheric observations